Conversation Analytic Perspectives to Digital Interaction Practices, Resources, and Affordances - Koivisto, Aino Loviisa; Vepsäläinen, Heidi; Virtanen, Mikko T. (Studia Fennica Linguistica, 2023)
This book offers a collection of state-of-the-art conversation analytic work on the impact of different types of digital technologies and media on social interaction. It furthers our understanding of whether and to what extent the varying practices of digital interaction can be considered adaptations of the basic organisations and resources of co-present face-to-face interaction. The chapters explore the emerging practices in contemporary digital interaction and in interaction related to digital technologies. The volume is organised into four sections according to the platform or type of digital interaction: mobile messaging, social media, video conferencing, and human-computer interaction. Each of the chapters highlights an interactional or linguistic phenomenon - an action, a practice, a sequence, or a larger structure. Some of these are unique to online environments, such as emojis or hashtags, whereas some occur in both online and offline interaction, such as repair initiators and proposal sequences.